2019
DOI: 10.1186/s13256-019-1985-z
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan and vincristine for the treatment of refractory desmoplastic small round cell tumor in a developing country: a case report

Abstract: Introduction Desmoplastic small round cell tumor is an extremely rare and aggressive cancer that affects mainly adolescents and young adults. Despite multiple therapeutic strategies, most patients have resistant disease with very poor survival rates. Case presentation We present a case of a 10-year-old Caucasian boy with a desmoplastic small round cell tumor refractory to conventional treatment who exhibited a good response to alternative treatment. With use of irinotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…DSCRT is characterized by the specific t(11;22)(p13;q12) translocation, with EWSR1-WT1 gene fusion in the majority of cases (18,19). By in situ hybridization, the identification of this characteristic fusion between exon 7 of EWSR1 and exon 8 of WT1 is therefore crucial in establishing diagnosis (19)(20)(21). EWSR1 is in fact the most frequent gene to partner with other genes to generate recurrent fusion genes in softtissue neoplasms associated with nonrandom chromosomal translocations (22).…”
Section: Discussionmentioning
confidence: 99%
“…DSCRT is characterized by the specific t(11;22)(p13;q12) translocation, with EWSR1-WT1 gene fusion in the majority of cases (18,19). By in situ hybridization, the identification of this characteristic fusion between exon 7 of EWSR1 and exon 8 of WT1 is therefore crucial in establishing diagnosis (19)(20)(21). EWSR1 is in fact the most frequent gene to partner with other genes to generate recurrent fusion genes in softtissue neoplasms associated with nonrandom chromosomal translocations (22).…”
Section: Discussionmentioning
confidence: 99%
“…While response to vincristine, irinotecan, and temozolomide has been reported in DSRCT, 8,13‐18 use of all three agents has not been described for this disease in combination with interval‐compressed therapy in the upfront setting. We found that VIT has activity against DSRCT, and in our cohort, no patient experienced disease progression while on therapy.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Responses to vincristine and irinotecan in DSRCT have been reported in the published literature, and this combination is active in many sarcomas. [13][14][15][16][17][18] Temozolomide has also been of interest in DSRCT given its radiosensitizing effects. 8 The Children's Oncology Group (COG) protocol ARST08P1, which was initially developed for children with high-risk rhabdomyosarcoma, evaluated interval-compressed vincristine/doxorubicin/ cyclophosphamide (VDC) alternating with cycles of ifosfamide/ etoposide (IE), cycles of vincristine/dactinomycin/cyclophosphamide (VAC), and either cycles of vincristine/irinotecan/temozolomide (VIT, Arm P2) or vincristine/irinotecan/cixutumumab (Arm P1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient was treated with Irinotecan. Some authors have shown that topoisomerase inhibitors, such as Irinotecan, can be effective in DSRCT [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%